CORE Learning Strategy in Islamic Education: A Solution to Students' Low Evaluation Skills - Murwani, Simping Setyo; Fatoni, Fatoni; Wahyudi, Waluyo Erry (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
Low learning outcomes and underdeveloped higher-order thinking skills (C5/evaluation) among students in Islamic Religious Education (PAI) remain a significant challenge, primarily because instruction is dominated by conventional methods that limit student engagement and hinder their involvement in analysis and evaluation. This study examines the application of the CORE (Connecting, Organizing, Reflecting, Extending) learning model as an innovative alternative strategy to enhance students' evaluative abilities. The purpose of this research was to determine the effect of the CORE model on PAI learning outcomes at SMP Negeri 1 Bandar Lampung. Employing a quantitative approach with a quasi-experimental design and a post-test only control group, the sample was selected through simple random sampling. The C5 cognitive test instrument used was validated and reliable. Results indicated a significant difference between the experimental and control groups (p = 0.001), demonstrating that the CORE model effectively improves fiqh learning outcomes, particularly students' evaluative skills. This finding contributes to the advancement of Islamic Religious Education (PAI) by integrating Qur'anic principles and socio-religious contexts, encouraging students to critically and reflectively connect fiqh concepts with Qur'anic values and everyday religious life.